Caffeine programs hepatic SIRT1-related cholesterol synthesis and hypercholesterolemia via A2AR/cAMP/PKA pathway in adult male offspring rats. (15th April 2019) - Hu, Shuwei; Liu, Kexin; Luo, Hanwen; Xu, Dan; Chen, Liaobin; Zhang, Li; Wang, Hui
Graphical abstract: Highlights: Prenatal caffeine exposure (PCE) induced adult hypercholesterolemia. Caffeine activated liver A2AR/cAMP/PKA pathway. Caffeine enhanced histone modifications of SREBP2, HMGCR and HMGCS. Abstract: Clinical and animal studies have indicated that hypercholesterolemia has intrauterine developmental origin. Our previous studies showed that prenatal caffeine exposure (PCE) increased the serum total cholesterol (TCH) levels in adult offspring rats. This study investigates the intrauterine programming mechanism of PCE male offspring rats susceptible to adult hypercholesterolemia. Pregnant Wistar rats were intragastrically administered caffeine (30, 60, and 120 mg/kg∙d) from gestational days (GD) 9 to 20. Male offspring were sacrificed under anesthesia at GD20 and postnatal week (PW) 12, and the serum and liver were collected. The effects of caffeine (0–100 μM, 24 h) on the expression of cholesterol synthesis related genes and their epigenetic mechanisms were confirmed in L02 cells. The results showed that PCE induced higher levels of serum TCH, LDL-C and higher ratios of TCH/HDL-C and LDL-C/HDL-C. Furthermore, the high levels of histone acetylation ( via H3K14ac and H3K27ac) and the expression of genes ( Srebf2, Hmgcr, Hmgcs1 ) were responsible for cholesterol synthesis. The results of PCE offspring in utero and the data in vitro exhibited similar changes, and accompanied by the reduced expression of adenosine A2A receptor ( A2AR ), cyclic adenosine monophosphate (cAMP), sirtuin1 and protein kinase A (PKA). These changes could be reversed by A2AR agonist (CGS-21680), cAMP agonist (forskolin) and sirtuin1 agonist (resveratrol). Therefore, our results confirmed that caffeine could enhance histone acetylation and expression levels of genes responsible for cholesterol synthesis via inhibiting the A2AR/cAMP/PKA pathway and down-regulating sirtuin1, which continued throughout adulthood and elevated hepatic cholesterol synthesis and hypercholesterolemia in the male offspring rats.